Univerza v Ljubljani na mednarodnih univerzitetnih košarkarskih tekmovanjih - Jamnik, Matej (Šport (Ljubljana), 2019)
In the article, I wanted to present the activities from the past five years (2013-2018) in the field of international university competition at the University of Ljubljana in the basketball branche. Due to various reasons, "activitiy" in this area has dropped significantly since 2009 (in the ten year period from 1999 to 2009, the University of Ljubljana received the prestigious award for the best university in Europe in the field of university competition). The goal was to try to return the University of Ljubljana through basketball activities to the European University Sports Map. In spite of all the efforts (the results were also very good in the overall evaluation), I have to mention that we were not completely successful (the return the University of Ljubljana to the European University Sports Map). In particular, I missed some general interest from the University of Ljubljana in one way or another. This way it would be much easier to establish cooperation with sports associations and their clubs in the future (consistency in the implementation of programs). Such mutual trust would undoubtedly improve the response of the players and their clubs, thereby increasing the contribution of the University of Ljubljana in developing them. In general, with such an approach, all programs of University Competition Sports would be "enriched", which would be welcome for everybody in this field (University of Ljubljana, sports teachers, and especially students).
Keywords: basketball; competitions; košarka; students; študenti; tekmovanja; UNI sport; University of Ljubljana; Univerza v Ljubljani; univerzitetni šport